The Economic Impact of Zebra Mussels in Florida - Donna J. Lee; Damian C. Adams; Frederick J. Rossi (EDIS)
FE-693, a 5-page illustrated fact sheet by Donna J. Lee, Damian C. Adams, and Frederick J. Rossi, reports results from a 20-year simulation model on the economic impacts of public investment in prevention and eradication of this bio-fouling organism which is expected to reach Florida in the near future, with particular attention to the effect on Lake Okeechobee. Includes references. Published by the UF Department of Food and Resource Economics, August 2007.